Social Exclusion and Conversion Factors: The case of Married International Graduate Students at One US University - Soylemez-Karakoc, Busra; Jiang, Xinhui; Hussain, Maryam (Journal of International Students, 2023)
Scholarship on international students shows that despite university policies designed to create a welcoming atmosphere, international students still face social challenges. This paper applies the capabilities approach to reveal mechanisms that facilitate or constrain the social inclusion of married international graduate students. For married international graduate students, the personal factors (their level of study and marital status) bring with structural factors (e.g., visa policies, healthcare policies, cultural and linguistic barriers), which in combination lead to social exclusion. With one university case study, including original survey and interview data, we unpack these intertwined processes and find that married graduate students’ social relation and network patterns significantly differ from single graduate students and undergraduate students. They are less likely to attend campus events, interact with their colleagues, and interact with friends from other countries. As such, we challenge the conventional wisdom that access to higher education alone leads to social inclusion.